أثر الدلالة الصرفية في بيان المعنى في جزء (عم) من خلال تفسير التحرير والتنوير - عبد الله, الصادق سالم (مجلة الاصالة, 2025)
أثر الدلالة الصرفية في بيان المعنى في جزء (عم) من خلال تفسير التحرير والتنوير